2010
DOI: 10.1093/cvr/cvq002
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole enhances ischaemia-induced arteriogenesis through an endocrine nitrite/nitric oxide-dependent pathway

Abstract: Dipyridamole augments nitrite/NO production, leading to enhanced arteriogenesis activity and blood perfusion in ischaemic limbs. Together, these data suggest that dipyridamole can augment ischaemic vessel function and restore blood flow, which may be beneficial in peripheral artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 46 publications
4
64
0
3
Order By: Relevance
“…Experimentally we have demonstrated that dipyridamole significantly restores hippocampally based spatial memory (Melani et al 2010) and has a protective effect on hippocampal CA1pyramidal neurons (Lana et al 2014) 90 days after 2VO. The increases of extracellular adenosine (Figueredo et al 1999), together with increased VEGF production (Ernens et al 2010), and the potentiation of the NO system (Aktas et al 2003;Venkatesh et al 2010) help explaining the protecting effect of dipyridamole in this rat model of hypoperfusion. Dipyridamole has a positive effect on blood flow and angiogenesis through the nitrite/NO endocrine system (Venkatesh et al 2010), increases NO levels and decreases superoxide formation both in ischemic and non-ischemic animals (Pattillo et al 2011), and has pleiotropic pharmacological effects, such as antioxidant and antiinflammatory proprieties (Blake 2004;Eisert 2002;Hsieh et al 2010;Riksen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally we have demonstrated that dipyridamole significantly restores hippocampally based spatial memory (Melani et al 2010) and has a protective effect on hippocampal CA1pyramidal neurons (Lana et al 2014) 90 days after 2VO. The increases of extracellular adenosine (Figueredo et al 1999), together with increased VEGF production (Ernens et al 2010), and the potentiation of the NO system (Aktas et al 2003;Venkatesh et al 2010) help explaining the protecting effect of dipyridamole in this rat model of hypoperfusion. Dipyridamole has a positive effect on blood flow and angiogenesis through the nitrite/NO endocrine system (Venkatesh et al 2010), increases NO levels and decreases superoxide formation both in ischemic and non-ischemic animals (Pattillo et al 2011), and has pleiotropic pharmacological effects, such as antioxidant and antiinflammatory proprieties (Blake 2004;Eisert 2002;Hsieh et al 2010;Riksen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The increases of extracellular adenosine (Figueredo et al 1999), together with increased VEGF production (Ernens et al 2010), and the potentiation of the NO system (Aktas et al 2003;Venkatesh et al 2010) help explaining the protecting effect of dipyridamole in this rat model of hypoperfusion. Dipyridamole has a positive effect on blood flow and angiogenesis through the nitrite/NO endocrine system (Venkatesh et al 2010), increases NO levels and decreases superoxide formation both in ischemic and non-ischemic animals (Pattillo et al 2011), and has pleiotropic pharmacological effects, such as antioxidant and antiinflammatory proprieties (Blake 2004;Eisert 2002;Hsieh et al 2010;Riksen et al 2005). Dipyridamole decreases the production of proinflammatory cytokines (Al Bahrani et al 2007), chemokines (Weyrich et al 2005), inhibits matrix metalloprotease-9 (Weyrich et al 2005), COX-2 activity (Chen et al 2006), and the neutrophil adhesion to endothelium (Chello et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study suggested that PKA activity is required for postnatal angiogenesis and ischemic angiogenesis (25,26). Thus, the elements of this Gab1-mediated PKA-dependent pathway, such as the binding sites on Gab1 for Shp2, Shp2, and PKA, may potentially be efficient therapeutic targets for pharmacological intervention to treat human ischemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse ischemic hindlimb model was established and evaluated as previously described (25,26) and is detailed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation